El compromiso laboral (engagement) en las áreas administrativas de un medio de comunicación escrito de la ciudad de Quito-Ecuador - Bravo Mantilla, Eduardo Agustín (2013)
In the area of professional organizations exist in the administrative areas that do not engage with work activities, being prone to a labor impasse or seeking new challenges. The proposal is to create psychology positive alternative techniques to target people who are committed to their work, identify levels of vigor, dedication and absorption using in their daily tasks. All these factors make the commitment or engagement work, which is a subject on which this study focuses mainly on the administrative areas of a media brief Quito. The sample that participated in this study consisted of people from the areas of accounting, treasury, human resources and call center…